Reconstruction of Severely Atrophic Pre-Maxilla Using Rhbmp-2 and Titanium Mesh for Dental Implants: A Case Report. - Cimara Fortes Ferreira; Jório da Escóssia; Tércio Pessoa Tabosa e Silva; André Luiz Zétola; Rodrygo Nunes Tavares (Journal of Dentistry And Oral Implants, 2015)
This case report details reconstruction of a severely atrophic pre‑maxilla using rhBMP‑2 and a titanium mesh framework. Surgical technique, graft outcomes, and implant rehabilitation are described, with notes on indications and complications.
Keywords: Bone graft